Assessment of different washing treatments to mitigate imidacloprid and acetamaprid residues in spinach. (21st January 2016) - Abdullah; Randhawa, Muhammad Atif; Akhtar, Saeed; Mansoor‐ul‐Hassan; Asghar, Ali; Sohaib, Muhammad; Aadil, Rana Muhammad; Jahangir, Muhammad Ahmar
Abstract: BACKGROUND: Agricultural crops treated with pesticides retain toxic residues that can cause various health disorders upon consumption. The present research project was designed to assess pesticide residues in contaminated spinach ( Spinacia oleracea ). The efficiency of chemical solutions (acetic acid, citric acid, hydrogen peroxide, sodium chloride and sodium carbonate) of different concentrations (% w/v) along with tap water for the dissolution of pesticide residues in spinach was studied. After various dipping treatments (T0 –T22 ) of treated spinach, imidacloprid and acetamaprid residues were determined by high‐performance liquid chromatography (HPLC). RESULTS: Among the solutions tested, the highest reductions in imidacloprid and acetamaprid residues respectively were 0.92 ± 0.04 mg kg −1 (83%) and 1.42 ± 0.53 mg kg −1 (87%) in treatment T6 (10% acetic acid), followed by 0.79 ± 0.01 mg kg −1 (69%) and 0.86 ± 0.05 mg kg −1 (71%) in treatment T11 (10% citric acid), while the lowest were 0.30 ± 0.02 mg kg −1 (27%) and 0.35 ± 0.02 mg kg −1 (29%) in treatment T20 (4% sodium carbonate). Moreover, treatment T1 (tap water) caused 0.27 ± 0.00 mg kg −1 (23%) and 0.38 ± 05 mg kg −1 (27%) elimination of imidacloprid and acetamaprid residues respectively. CONCLUSION: From these findings it is inferred that acetic acid and citric acid washing treatments can be used along with tap water to minimize pesticide residues in treated vegetables. © 2015 Society of Chemical Industry